Information management in organizations in 2012: perspectives and trends - Cobarsí-Morales, Josep (Anuario ThinkEPI, 2013)
The increase in technological capabilities in information handling has raised a number of security and privacy issues with growing importance at the corporate level. On the other hand, aspects such as the implementation of the ISO 30300 series and innovative procurement projects pose new challenges and opportunities for document management and competitive intelligence, respectively. All this points to the issue of how to reformulate intermediation and the corresponding professional role in the organizational environment.